2016
DOI: 10.1097/bpo.0000000000000454
|View full text |Cite
|
Sign up to set email alerts
|

Do Surgical Times and Efficiency Differ Between Inpatient and Ambulatory Surgery Centers That are Both Hospital Owned?

Abstract: Level III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
25
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(28 citation statements)
references
References 9 publications
2
25
0
1
Order By: Relevance
“…Although surgeries performed at ASCs are reimbursed at a lower rate than those performed at HOPDs, ASCs maintain their financial solvency through greater efficiency and patient throughput and lower turnover times, resulting in increased surgical volume. 3,23 This is particularly beneficial for relatively quick surgeries like cataract extraction; many surgeries can be performed on a given day at a single ASC. Ambulatory surgery centers are more convenient than HOPDs for many patients because they are often closer to patients' homes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although surgeries performed at ASCs are reimbursed at a lower rate than those performed at HOPDs, ASCs maintain their financial solvency through greater efficiency and patient throughput and lower turnover times, resulting in increased surgical volume. 3,23 This is particularly beneficial for relatively quick surgeries like cataract extraction; many surgeries can be performed on a given day at a single ASC. Ambulatory surgery centers are more convenient than HOPDs for many patients because they are often closer to patients' homes.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Reasons for the increasing popularity of ASCs relative to HOPDs include enhanced surgeon productivity, improved convenience for patients and surgeons, decreased out-of-pocket patient costs, and decreased per-case costs for insurers. [3][4][5] An advantage of performing surgeries at HOPDs rather than ASCs is that when HOPDs are attached to hospitals, they are often better equipped to deal with medical emergencies. 6 To curtail rising surgical care costs, some insurers have considered incentivizing patients to undergo surgery at ASCs rather than HOPDs.…”
mentioning
confidence: 99%
“…In this prior study, the efficiency of a hospital inpatient facility was found to be inferior to that of its own ASC. 43 Orthopedic procedures by the same surgeon were performed more efficiently and more rapidly at the ASC than the inpatient facility. In this reported scenario, both the inpatient and ambulatory facilities were owned and operated by the same hospital without financial incentive to the operating surgeon.…”
Section: Discussionmentioning
confidence: 99%
“…An effort to minimize resource utilization and improve surgical efficiency not only requires optimization of existing protocols, but also innovation of medical practice through implementation of telemedicine services and transition to same-day surgery, where patients are discharged on the day of surgery. [8] Previous studies have demonstrated the safety and efficacy of same-day mastectomy and breast reconstruction, largely relying on extensive perioperative planning and postoperative recovery protocols to simplify surgical course and minimize patient morbidity [9][10][11]. Prior implementation of an enhanced recovery protocol at our institution has decreased the need for opioid analgesia and length of hospital stay following mastectomy and implant-based breast reconstruction, thereby limiting the need for inpatient admission during the immediate postoperative period [12].…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%